BORC assemblies integrate BLOC-1 subunits to diversify endosomal trafficking functions - Mariana E. G. de Araujo; Sascha J. Amann; Taras Stasyk; Alexander Schleiffer; Eva Rauch; Paula Flümann; Isabel I. Singer; Leopold Kremser; Vojtech Dostal; Thanida Laopanupong; Nikolaus Obojes; Moritz H. Wallnöfer; et al. (Proceedings of the National Academy of Sciences, 2026)
BORC and BLOC-1 are multisubunit complexes that regulate endolysosomal trafficking. Although they are presumed to be distinct, their paralogous origins and shared subunits suggest the potential for higher-order assembly. Here, we reveal the conserved octameric architecture of BORC formed by two intertwined tetramers and present the structure of C. elegans BORC. Through cross-linking mass spectrometry of endogenous complexes, we validate this model for human BORC and demonstrate that the integrity of the complex, which is essential for lysosomal transport, relies on specific interfacial residues. We also clarify the disruptive nature of disease-causing mutations and propose that the formation and function of BORC are likely regulated by specific cues. These cues might include the phosphorylation of Snapin and a pH-sensitive histidine residue in BORCS5. Additionally, we present direct biochemical and structural evidence of BORC–BLOC-1 hybrid complexes. Finally, we link a specific hybrid complex to the regulation of transferrin receptor recycling via interaction with the EARP complex. Our work challenges the paradigm of BORC and BLOC-1 as separate entities, establishing a model of dynamic complex formation wherein modular assembly creates functional specialization to meet diverse cellular demands.